Interaction of DNA/polycation complexes with phospholipids: stabilizing strategy for gene delivery - Zintchenko, Arkadi; Konák, Cestmír (Macromolecular bioscience, 2005)
The interaction between negatively charged lipid vesicles and positively charged DNA/polylysine complexes was studied. The interaction does not lead to release of DNA from the initial complexes. The particles formed are easy to prepare, they have slight negative charge, small dimensions and show good stability in physiological NaCl solution. Such properties might indicate that stabilization of the particles by lipid coating might be a potent strategy, alternative to PEGylation of DNA/polycation complexes. Interaction of DNA/polycation complex particles with lipid vesicles.
Keywords: technika přenosu genů; Lipid Bilayers; roztoky; kationty; sérový albumin; Solutions; chlorid sodný; Cations; Nanostructures; Serum Albumin; nanostruktury; Polylysine; DNA; polylysin; lipidové dvojvrstvy; Phospholipids; fosfolipidy; Sodium Chloride; Gene Transfer Techniques